2014
DOI: 10.1093/ejcts/ezu012
|View full text |Cite
|
Sign up to set email alerts
|

Key success factors for thoracic endovascular aortic repair for non-acute Stanford type B aortic dissection

Abstract: The early results of TEVAR for non-acute Stanford type B aortic dissection were favourable. However, for cases with patent false lumens, complete obliteration of the false lumen of the entire aorta was difficult to achieve. Absence of the primary entry at the outer curvature of the distal aortic arch, younger age, small aortic diameter and absence of the abdominal aortic branches arising from the false lumen were the key success factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…For TEVAR, elective interventions ranged between 62.5% and 100.0% [ 21 , 28 , 38 , 45 , 46 , 52 ], urgent operations between 18.8% and 97.2% [ 21 , 28 , 41 ], and emergency procedures were performed between 2.0% and 18.8% [ 21 , 28 , 41 , 43 , 45 , 46 , 49 , 51 , 52 ]. Reported time intervals from incident dissection to TEVAR ranged between a median of 3 weeks up to 36.0 months [ 21 , 34 , 36 , 44 , 46 ] and a mean of 3 weeks and 53.8 months [ 29 , 33 , 37 , 38 , 40 , 43 , 45 , 49 , 50 ]. Mean time to intervention was 24.4 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For TEVAR, elective interventions ranged between 62.5% and 100.0% [ 21 , 28 , 38 , 45 , 46 , 52 ], urgent operations between 18.8% and 97.2% [ 21 , 28 , 41 ], and emergency procedures were performed between 2.0% and 18.8% [ 21 , 28 , 41 , 43 , 45 , 46 , 49 , 51 , 52 ]. Reported time intervals from incident dissection to TEVAR ranged between a median of 3 weeks up to 36.0 months [ 21 , 34 , 36 , 44 , 46 ] and a mean of 3 weeks and 53.8 months [ 29 , 33 , 37 , 38 , 40 , 43 , 45 , 49 , 50 ]. Mean time to intervention was 24.4 months.…”
Section: Resultsmentioning
confidence: 99%
“…Mean time to intervention was 24.4 months. Indications for TEVAR were aortic aneurysm (74.5% to 100.0%) [ 28 , 32 , 35 , 37 , 43 , 45 , 48 , 49 ], failure of OMT (12.3%) [ 32 ], rupture (2.7% to 10.0%) [ 32 , 35 , 41 , 43 , 46 , 49 ], rapid aortic enlargement (11.8% to 100.0%) [ 28 , 37 , 41 , 43 , 49 ], recurrent/refractory pain (4.3% to 57.7%) [ 32 , 37 , 41 , 43 , 49 ], malperfusion (2.5% to 18.8%) [ 32 , 41 , 46 , 49 ], patent false lumen (FL) (64.2%) [ 40 ] and other indications (6.6% to 23.5%) [ 37 , 40 , 49 ]. Double indications could be present in a single patient.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Tsai et al [66] showed that a proximal location of the entry tear may cause aortic expansion. In the series by Kitamura et al [67], the primary entry at the outer curvature of the distal aortic arch was associated with a lower chance of thrombosis of the descending false lumen, and a primary entry at the inner curvature of the distal aortic arch was associated with a higher risk of complication in acute TBAD [33,68].…”
Section: Entry Tearmentioning
confidence: 92%
“…These may include an aortic diameter of > 44 mm at diagnosis, partial false lumen thrombosis, false lumen diameter of > 22 mm (100% sensitive, 76% specific), location of primary entry tear on the under surface of the arch or on its medial aspect, width of entry tear > 10 mm, elliptical shape of true lumen, circular false lumen, crosssectional area of false lumen to true lumen of > 0.7, and a spiral configuration of the dissection (►Table 3). [32][33][34][35][36][37] Dissection is classified as complicated (►Table 4) if it is associated with refractory pain; malperfusion; rupture, free, or contained; hypertension that is associated with malperfusion or persistent despite full medical therapy; increase in periaortic hematoma; and hemorrhagic pleural effusion in two CT examinations, suggesting an impending rupture. 38,39 Moreover, refractory pain and persistent hypertension are associated with an increased mortality.…”
Section: Treatmentmentioning
confidence: 99%